2021
DOI: 10.1177/0010414021997174
|View full text |Cite
|
Sign up to set email alerts
|

How Political Careers affect Prime-Ministerial Performance: Evidence from Central and Eastern Europe

Abstract: Even though Prime Ministers (PMs) are the central actors in parliamentary democracies, little comparative research explores what makes them perform successfully in office. This article investigates how the political careers of PMs affect their performance. For this purpose, we make use of a unique expert survey covering 131 cabinets in 11 Central and Eastern European countries between 1990 and 2018. Performance is defined as a two-dimensional set of tasks PMs ought to fulfill: first, managing the cabinet and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…According to our findings, changes in ministers who belong to the PM's coalition partners appear to induce the highest cost for her performance, while changes in ministers from her party or those in charge of core portfolios are less consequential. These results add to our understanding of the intra-cabinet determinants of prime-ministerial performance and enrich the extant literature that focused on the effects of PMs' careers (Grotz et al 2021) as well as their relationships with their principalsthat is, the parliamentary majority and their own parties (Samuels and Shugart 2010;Strangio et al 2013).…”
supporting
confidence: 52%
See 3 more Smart Citations
“…According to our findings, changes in ministers who belong to the PM's coalition partners appear to induce the highest cost for her performance, while changes in ministers from her party or those in charge of core portfolios are less consequential. These results add to our understanding of the intra-cabinet determinants of prime-ministerial performance and enrich the extant literature that focused on the effects of PMs' careers (Grotz et al 2021) as well as their relationships with their principalsthat is, the parliamentary majority and their own parties (Samuels and Shugart 2010;Strangio et al 2013).…”
supporting
confidence: 52%
“…Third, our article sheds new light on the differentiated impact of government stability in the post-communist democracies of CEE where cabinets have been relatively short-lived compared to Western democracies (Grotz and Weber 2012;Somer-Topcu and Williams 2008). While previous research found that prime-ministerial performance does not strongly correlate with cabinet duration in the CEE context (Grotz et al 2021), our analysis shows that it is significantly affected by the frequency of ministerial turnover. Hence, the findings contribute to the debate on which forms of government instability are more detrimental for the functioning of political executives (Huber 1998;Huber and Martinez-Gallardo 2008).…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In this regard, Table 3 provides data about trends of political experience over the centuries. Following an established path in the study of political careers and chief executives' political performance, experience is simply operationalised as having occupied major political offices before being elected (see Grotz et al 2021).…”
Section: Stability and Change In The Career Background Of American Pr...mentioning
confidence: 99%